2019
DOI: 10.1097/ana.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthesia on Long-term Outcomes in Patients With Supratentorial High-grade Glioma Undergoing Tumor Resection: A Retrospective Cohort Study

Abstract: Background: Intravenous and inhalational anesthesia might have different associations with long-term outcome in cancer patients, with reports of adverse effects of inhalation anesthesia. However, the effects of anesthesia in patients with high-grade glioma (HGG) are not known. Methods: This study investigated 154 patients who received propofol and 140 patients who received sevoflurane for maintenance of anesthesia during HGG tumor resection. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 34 publications
2
51
0
Order By: Relevance
“…One might criticize the cohort size as being too small to reveal smaller effects; however, the completely identical course until progression, even when potentially calculated for larger cohorts, would make a clinically relevant effect highly improbable. Our observation is in line with a recent retrospective analysis comparing high-grade glioma patients receiving propofol or sevoflurane for maintainance which also showed no significant difference in progression free or overall survival 16 . However, a standardized therapy for glioblastomas is only defined for primary treatment.…”
Section: Scientific Reports |supporting
confidence: 92%
“…One might criticize the cohort size as being too small to reveal smaller effects; however, the completely identical course until progression, even when potentially calculated for larger cohorts, would make a clinically relevant effect highly improbable. Our observation is in line with a recent retrospective analysis comparing high-grade glioma patients receiving propofol or sevoflurane for maintainance which also showed no significant difference in progression free or overall survival 16 . However, a standardized therapy for glioblastomas is only defined for primary treatment.…”
Section: Scientific Reports |supporting
confidence: 92%
“…13 Recently, one study found that in patients with high-grade glioma undergoing cancer surgery, intraoperative use of propofol or sevoflurane anaesthesia led to no difference in OS or progression-free survival (PFS). 14 In the study by Oh et al, 15 among patients who underwent gastric cancer surgery, there was no difference in cancer-related mortality after using propofol or inhalation anaesthesia. Nonetheless, these findings are retrospective and have some important limitations.…”
Section: Effec T Of Prop Ofol On the Prog Nos Is Of Patients With Cmentioning
confidence: 95%
“…8,9 Furthermore, compared with the propofol group, the sevoflurane group displayed a higher rate of cancer recurrence in breast cancer patients undergoing modified radical mastectomy, 10 and increased the risk of death in patients with high-grade glioma undergoing tumor resection. 11 But recently, a randomized control trial involved in more than 2000 women who underwent breast cancer surgery demonstrated that there was no significant difference in breast cancer recurrence rate among women receiving general anesthesia (sevoflurane and opioids) and regional anesthesia analgesia (paravertebral block and propofol). 12 Therefore, according to published reports, compared with propofol, sevoflurane might have no effect on the prognosis of breast cancer patients during the surgery, but it could have an unfavorable effect on the outcomes of patients with other cancers, which need further investigation.…”
Section: Sevoflurane and Cancer The Effect Of Sevoflurane On Clinicalmentioning
confidence: 99%